Single-Leg Structural Design and Foot Trajectory Planning for a Novel Bioinspired Quadruped Robot. (12th January 2021) - Chen, Mingfang; Li, Qi; Wang, Sen; Zhang, Kaixiang; Chen, Hao; Zhang, Yongxia
Abstract : To meet the stability requirements for moving quadruped robots, it is important to design a rational structure for a single leg and plan the trajectory of the foot. First, a novel electrically driven leg mechanism for a quadruped robot is designed in this paper to reduce the inertia of the leg swing. Second, a modified foot trajectory based on a compound cycloid is proposed, which has swing-back and retraction motion and continuous velocity in the x -axis direction. Third, a Simulink platform is built to verify the correctness of the proposed foot trajectory. The simulation result shows that when the flight phase and the stand phase switch, the impact of torque is smaller than the foot trajectory before modification. Finally, an experimental platform is constructed, and a control algorithm is written into the controller to realize the foot proposed trajectory. The results of the experiment prove the feasibility of the leg mechanism and the rationality of the proposed foot trajectory.